Participatory Action dalam Pengembangan Kreativitas Kegiatan Pelepasan Siswa-Siswi di Taman Kanak-Kanak Kanisius Gendongan - Debra Tara Kania Simon Harun; Salisa br Sembiring; Mozes Kurniawan (Universitas Kristen Satya Wacana Salatiga, 2022)
This year's TK B student release activities are organized by the school, and this year is no exception. This program is held with the aim of giving awards to children as a symbol of graduation, giving a good impression, establishing intimacy with parents and as a sign of gratitude for entrusting their children to be educated by the school. This community service activity is focused on evaluating the activities of releasing Kindergarten B students and contributing ideas to the school. The object of the activity is Kanisius Gendongan Kindergarten Salatiga. The service technique is done by participatory action; the community service team observes and contributes to the management of the release and distribution of Kindergarten B student report cards, interviews, evaluations, and contributes ideas that are useful for the object of activity.